Influence Clarity Target Budget, Control Accounting, and Systems Reporting to Performance Accountability - Abidin, Abinayla nayla; Rahmawati, Rahmawati; Junaidi, Junaidi (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This research aims to analyze the influence of clarity of budget objectives, accounting control, and reporting systems on performance accountability in government agencies. Design/methodology/approach: The respondents in this study were staff in all sections of one government agency, the secretariat of the Palopo City DPRD. This research uses a causality-based quantitative method through distributing questionnaires. The population in this study were employees who worked at the Palopo City DPRD Secretariat with a sampling technique using saturated sampling (census), which means sampling utilized the entire population. The data were analyzed using SPSS software. Findings: The results of this research show that clarity of budget targets, accounting controls, and reporting systems have a positive and significant effect on performance accountability. Paper type: Research paper.